Global Governance on Renewable Energy: Contrasting the Ideas of the German and the Brazilian Governments - Roehrkasten, Sybille (Springer, 2015)
Comparing Germany’s and Brazil’s government perspectives, Sybille Roehrkasten reveals that the ideas on global renewable energy governance are highly contested. In her study, the author sheds light on the politics behind the definition of global governance issues, focusing on two pioneers in the worldwide promotion of renewables and two decisive players in this emergent area of global cooperation. She demonstrates that ideas about problems and solutions in transboundary policy-making differ widely and that these differences are caused by the decision makers’ policy contexts and self-interests. The differences concern key aspects in global governance on renewables, such as global challenges to be addressed, favored renewables options, barriers to renewables promotion and tasks for cooperation.